Gut microbiome: a novel preventive and therapeutic target for prostatic disease - Cao, Hongliang; Zhang, Difei; Wang, Pengyu; Wang, Yishu; Shi, Chengdong; Wu, Hao; Du, Hao; Zhang, Wenqiang; Gou, Zixuan; Zhou, Honglan; Wang, Song (Frontiers in Cellular and Infection Microbiology, 2024)
The human gut microbiome (GM) impacts various physiological processes and can lead to pathological conditions and even carcinogenesis if homeostasis is disrupted. Recent studies have indicated a connection between the GM and prostatic disease. However, the underlying mechanisms are still unclear. This review aims to provide a summary of the existing information regarding the connection between the GM and various prostatic conditions such as chronic prostatitis/chronic pelvic pain syndrome (CP/CPPS), benign prostatic hyperplasia (BPH), and prostate cancer (PCa). Furthermore, the review aims to identify possible pathogenic mechanisms and suggest potential ways of targeting GM to prevent and treat prostatic disease. Due to the complexity of the mechanism between GM and prostatic diseases, additional research is required to comprehend the association between the two. This will lead to more effective treatment options for prostatic disease.